All Days 2006
DOI: 10.2118/103156-ms
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Shale Inhibition During Openhole Gravel Packing With Water-Based Fluids

Abstract: Many of the problems associated with the use of water based fluids in drilling and completion operations are caused by incompatibilities between the fluids and the shales. Such incompatibilities may result in washouts, increased drilling costs (solids handling, rig time, dilution fluids, dilution fluids), shale sloughing during the drilling operation and during the drilling operation and after displacements to solids-free completion completion fluids or during gravel packing. One of the most important factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A dynamic testing technique (Shenoy et al, 2006) confirmed that the shales tested were not significantly sensitive to correctly formulated water based fluids of the type being used. Although the shales were found to be much less reactive than feared, it was concluded that glycol inhibition was sub-optimal in the RDF used for both ENA01 and ENA02H.…”
Section: Shales -Mechanical and Chemical Stabilitymentioning
confidence: 88%
“…A dynamic testing technique (Shenoy et al, 2006) confirmed that the shales tested were not significantly sensitive to correctly formulated water based fluids of the type being used. Although the shales were found to be much less reactive than feared, it was concluded that glycol inhibition was sub-optimal in the RDF used for both ENA01 and ENA02H.…”
Section: Shales -Mechanical and Chemical Stabilitymentioning
confidence: 88%